PERSEPSI MASYARAKAT TERHADAP PROGRAM KAMPUNG IKLIM (PROKLIM) KELURAHAN TANGKERANG LABUAI KECAMATAN BUKIT RAYA KOTA PEKANBARU - Wahyu Setiawan; Jimmi Copriady; Dedi AfandI (Universitas Pahlawan, 2019)
This research was conducted in RW 04, Tangkerang Labuai, Bukit Raya District, Pekanbaru City. The purpose of this study is to analyze the level of community knowledge, community attitudes, community motivation and identify constraints related to climate in Tangkerang Labuai in terms of Garbage management activities. The research approach used in this study is a quantitative descriptive with the survey method. Based on the results of the research, the level of knowledge, attitudes and motivation for the value of errors obtained from the results of statistical calculations is smaller than the alpha value, which means that there is an influence between the level of knowledge, attitudes and motivations towards community perceptions regarding the climate village program in RW 04, Tangkerang Village Labuai, Bukit Raya District, Pekanbaru City. Constraints in implementing Proklim in Tangkerang Labuai are the facilities and infrastructure still insufficient, the government has not provided much contribution or assistance to Proklim's activities, while the formation of cadres in carrying out Proklim activities has not been maximized. Public perception related to the climate village program (Proklim) in RW 04, Tangkerang Labuai Village, Bukit Raya Subdistrict, Pekanbaru City has been very good.